2014
DOI: 10.1038/ng.3079
|View full text |Cite
|
Sign up to set email alerts
|

Common variants near ABCA1, AFAP1 and GMDS confer risk of primary open-angle glaucoma

Abstract: Primary open-angle glaucoma (POAG) is a major cause of irreversible blindness worldwide. We performed a genome-wide association study in an Australian discovery cohort comprising 1,155 advanced POAG cases and 1,992 controls. Association of the top SNPs from the discovery stage was investigated in two Australian replication cohorts (total 932 cases, 6,862 controls) and two US replication cohorts (total 2,616 cases, 2,634 controls). Meta-analysis of all cohorts revealed three novel loci associated with developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
164
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 197 publications
(179 citation statements)
references
References 45 publications
6
164
0
9
Order By: Relevance
“…Classic twin studies in POAG are lacking and there is no consensus on heritability for POAG, but work by Cuellar-Partida et al estimated the heritability of POAG based on genome-wide array data at 0.42 6 0.09 (6). Several genome-wide association studies (GWAS) have identified new POAG genes by examining POAG directly or studying endophenotypes like VCDR and IOP (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Several genes associated with VCDR and IOP -CDKN2B-AS1, SIX6 (VCDR); and CAV1/CAV2, TMCO1, ABCA1 and ARHGEF12 (IOP) -are associated with POAG.…”
Section: Introductionmentioning
confidence: 99%
“…Classic twin studies in POAG are lacking and there is no consensus on heritability for POAG, but work by Cuellar-Partida et al estimated the heritability of POAG based on genome-wide array data at 0.42 6 0.09 (6). Several genome-wide association studies (GWAS) have identified new POAG genes by examining POAG directly or studying endophenotypes like VCDR and IOP (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Several genes associated with VCDR and IOP -CDKN2B-AS1, SIX6 (VCDR); and CAV1/CAV2, TMCO1, ABCA1 and ARHGEF12 (IOP) -are associated with POAG.…”
Section: Introductionmentioning
confidence: 99%
“…European ancestry populations (CAV1 [150], CDKN2BAS [151], TMCO1 [151], SIX1 [152], ABCA1 [153,154], GMDS [154], AFAP1 [154]) were removed. For AMD, we removed loci from 35 loci summarized in Fritsche et al [305].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, 7 loci of relatively small effect have been implicated in POAG [150][151][152][153][154]. At genome-wide significant level only the ATPbinding cassette transporter ABCA1 is associated with both diseases [154,305].…”
Section: Conflicts Of Interestsmentioning
confidence: 99%
See 2 more Smart Citations